PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN SERTA LOYALITAS PETAMBAK UDANG INTENSIF KAWASAN TAPAL KUDA JAWA TIMUR - Masrurul Hudah; Bambang Irawan; Handriyono Handriyono (STIE Mandala Jember, 2017)
The shrimp is one of Indonesia's main export commodity. Since 2004 intensive shrimp farmers cultivation of vannamei shrimp. Intensification of shrimp farms require of quality and quantity of fry. This study aimed to analyze the influence of marketing mix variables on purchase decision and satisfaction and loyalty intensive shrimp farmers in purchasing shrimp fry to the hatchery. The marketing mix consists of variables: product, price, distribution, promotion, people, physical evidence, process. This research is an explanatory research and confirmatory study with a sample of intensive shrimp farmers horseshoe area of East Java. Analysis of causal relationships between variables and test research hypotheses using SEM (Structural Equation Modeling). Research results shows that marketing mix variables that influence purchase decisions are price, people, physical evidence and that affects customer satisfaction is product, price, distribution, people, processes and purchasing decisions affect the satisfaction and loyalty of farmers and also satisfaction effect on loyalty. Shrimp hatchery needs to pay attention to their marketing mix strategies to influence purchasing decisions and get the satisfaction and loyalty of farmers as their consumers.